The role of immune mechanisms in hypertension and advances in immunomodulatory research - XiaoLi Chen; Ling Sun; Ke Xuan; Aifen Zong (Clinical and Experimental Hypertension, 2025)
Hypertension is one of the major risk factors for cardiovascular diseases and end-organ damage worldwide. Traditionally, it has been linked to factors such as genetics, diet, and lifestyle. However, increasing research indicates that the immune system also plays an important role in the initiation and progression of hypertension. In the initiation phase, pro-hypertensive stimuli including chronic sympathetic nervous system (SNS), high salt intake and imbalanced gut microbes all influence the function of immune cells, contributing to the development of elevated blood pressure. As hypertension progresses, many immune cells, such as macrophages, dendritic cells, NK cells, B and T lymphocytes, accumulate in organs such as the heart, blood vessels, and kidneys. These cells release effector cytokines and reactive oxygen species, exacerbating tissue damage and organ dysfunction. Meanwhile, numerous studies suggest that intervening in immune inflammatory processes has the potential to regulate blood pressure and prevent damage to vital organs. This review aims to explore the role of immune regulation in various stages of hypertension and the progress of research on immune interventions for hypertension treatment, with the aim of providing new perspectives and approaches for future research and treatment of hypertension.